Major signal increase in fluorescence microscopy through dark-state relaxation. - Donnert, G; Eggeling, C; Hell, S (2007)
We report a substantial signal gain in fluorescence microscopy by ensuring that transient molecular dark states with lifetimes >1 micros, such as the triplet state relax between two molecular absorption events. For GFP and Rhodamine dye Atto532, we observed a 5-25-fold increase in total fluorescence yield before molecular bleaching when strong continuous-wave or high-repetition-rate pulsed illumination was replaced with pulses featuring temporal pulse separation >1 micros. The signal gain was observed both for one- and two-photon excitation. Obeying dark or triplet state relaxation in the illumination process signifies a major step toward imaging with low photobleaching and strong fluorescence fluxes.